INTERNAL SENSES IN NICHOLAS OF CUSA'S PSYCHOLOGY. - Fiamma, Andrea (Revista Española de Filosofía Medieval, 2020)
This paper considers Nicholas of Cusa's interpretation of Aristotle's De anima with regard to the functioning of the internal senses in the gnoseological process: sensus communis, vis memorialis, vis aestimativa, phantasia and vis imaginativa. For the first time in the recent historiography on medieval theory of knowledge, the references to the Aristotelian doctrine of the internal senses in Nicholas of Cusa's work are organized in a systematic and ordered philosophical reconstruction; as main source of the Cusanian doctrine of internal senses, Albert the Great's Liber de anima is identified.